Correlation Of Neutrophil Lymphocyte Ratio (NLR) Value With Incidence Of Tuberculosis Disease In Patients With Diabetes Mellitus - Istiqomah Istiqomah; Suhariyadi Suhariyadi; Evy Diah Woelansari (Poltekkes Kemenkes Mataram, 2024)
Diabetes mellitus is a non-communicable disease (PTM) that is chronic and can weaken the immune system so that sufferers are 3 times more likely to suffer from pulmonary TB. In chronic infection there is continuous inflammation which is characterized by the presence of neutrophils themselves and will be followed by low lymphocyte values due to immune system pathways that do not work perfectly. The purpose of this study was to determine the correlation between the Neutrophil Lymphocyte Ratio (NLR) and the incidence of Tuberculosis in Diabetes Mellitus patients at the Jorongan Health Center, Probolinggo Regency. This research is a correlative analytic study with a cross sectional approach. A total of 30 samples of diabetes mellitus patients at the Jorongan Health Center from January to April 2023. The NLR examination method was with a hematology analyzer and tuberculosis patients were examined using Molecular Rapid Test. The statistical test uses Spearman's nonparametric test. The results showed that there was a correlation between NLR values and the incidence of tuberculosis in diabetes mellitus patients at the Jorongan Health Center, p = 0.003 and r = 0.521. Further research needs to be carried out involving larger samples and other laboratory tests related to the immune system in patients with diabetes mellitus.